Improving Medication Understanding and Adherence Using Principles of Memory and Metacognition. (October 2018) - Hargis, Mary B.; Castel, Alan D.
More than half of older adults regularly take multiple medications. Rates of medication nonadherence are high, which undermines both patients' health and the economy. Memory and metacognitive factors (such as misplaced confidence) help explain why patients across the life span may not understand or follow prescribed regimens. These factors include difficulties in remembering confusing information, patients' and practitioners' potential overconfidence in memory, and misunderstandings about memory. Patients, practitioners, and the public can use these principles to improve memory, enhance understanding, and promote metacognitive accuracy with respect to complex medication information, which may increase the likelihood of adherence.